The Influence of Marketing Ability, Innovation Ability and Learning Ability on the Performance of SMEs in the Province of DIY - Muhammad Muhlisin (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
This study examines the influence of marketing capability, innovation capability and learning capability on the performance of SMEs in the DIY Province. The population of this study is SMEs in the DIY. The subjects of this study are employees, managers and/or owners of SMEs. The research sample of 176 respondents includes employees, managers and/or owners of SMEs in the City of Yogyakarta. The research data were then analyzed using multiple linear regression analysis. Based on the research results: First, marketing capability has a positive and significant effect on SME performance. Second, innovation capability has a positive and significant effect on SME performance. Third, learning capability has a positive and significant effect on SME performance. Fourth, marketing capability, innovation capability and learning capability have a positive and significant effect on SME performance in the DIY Province.